Juridical Analysis of State-Owned Enterprises (BUMN) with Bankruptcy Status - Zulfahmi Yusuf (JUSTICES: Journal of Law, 2024)
Bankrupt BUMN is not as simple as bankruptcy of a person or other legal entity, because this BUMN has state assets whose management must involve state intervention. Government intervention is proven by the presence of the Minister of Finance as CFO and majority owner of BUMN and the Minister of BUMN as director and supervisor of BUMN activities, apart from that there are supporting regulations, namely the KN Law, PN Law and Constitutional Court Decision No. 62/PUU-XI/2013 which notes that wealth separated from BUMN remains state wealth. If a state company is bankrupted by its own debtor, the finance minister has the largest say in the state-owned bankruptcy application than the GMS, in Peru the finance minister has the highest power and is the only party. who can file bankruptcy. The legal consequence of BUMN bankruptcy is that a public confiscation is carried out, but first the BUMN must go through a process of paying state assets in accordance with Minister of Finance Regulation No. 50/PMK.06/2014 because BUMN goods are still considered state-owned goods.